The Influence of Product Quality, Social Media Creative Content and Consumer Testimonials on Purchasing Decisions - Aulia Safira Andrianti; Kumara Adji Kusuma (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of product quality, social media creative content, and consumer testimonials on the purchase decision. Consumers of the Pilotter brand identified as popular in the study include those who use social media and have previously purchased products, as well as those between the ages of 12 and 40 who frequently visit Sidoarjo and make purchases from P's online and offline stores. This study uses a quantitative approach with the Partial Least Square (PLS) method and involves 100 respondents who are Pilotter consumers. Evaluation of the Inner Model (structural model) is carried out by calculating the values of R-Square, Q-Square, and F-Square. R-Square measures how much the variation of the change of independent variables affects the dependent variable, while Q-Square is used to determine the predictive relevance of the research through the blindfolding procedure. The results of the analysis showed that product quality did not have a significant effect on purchasing decisions, while social media creative content and consumer testimonials had a positive and significant influence. This shows that digital marketing strategies through social media and customer reviews play a greater role in attracting consumer interest than the quality factor of the product itself. Therefore, companies are advised to strengthen their digital marketing strategies and manage customer testimonials optimally to increase competitiveness and sales.